A Meiosis-Specific Form of the APC/C Promotes the Oocyte-to-Embryo Transition by Decreasing Levels of the Polo Kinase Inhibitor Matrimony - Whitfield, Zachary J. (Public Library of Science, 2013)
Oocytes are stockpiled with proteins and mRNA that are required to drive the initial mitotic divisions of embryogenesis. But are there proteins specific to meiosis whose levels must be decreased to begin embryogenesis properly? The Drosophila protein Cortex (Cort) is a female, meiosis-specific activator of the Anaphase Promoting Complex/Cyclosome (APC/C), an E3 ubiquitin ligase. We performed immunoprecipitation of Cortex followed by mass spectrometry, and identified the Polo kinase inhibitor Matrimony (Mtrm) as a potential interactor with Cort. In vitro binding assays showed Mtrm and Cort can bind directly. We found Mtrm protein levels to be reduced dramatically during the oocyte-to-embryo transition, and this downregulation did not take place in cort mutant eggs, consistent with Mtrm being a substrate of APC(Cort). We showed that Mtrm is subject to APC(Cort)-mediated proteasomal degradation and have identified a putative APC/C recognition motif in Mtrm that when mutated partially stabilized the protein in the embryo. Furthermore, overexpression of Mtrm in the early embryo caused aberrant nuclear divisions and developmental defects, and these were enhanced by decreasing levels of active Polo. These data indicate APC(Cort) ubiquitylates Mtrm at the oocyte-to-embryo transition, thus preventing excessive inhibition of Polo kinase activity due to Mtrm's presence.